2003
DOI: 10.1103/physrevlett.91.046403
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Independent Origin of the Strongly Enhanced Effective Mass in a Dilute 2D Electron System

Abstract: We have accurately measured the effective mass in a dilute two-dimensional electron system in silicon by analyzing temperature dependence of the Shubnikov-de Haas oscillations in the lowtemperature limit. A sharp increase of the effective mass with decreasing electron density has been observed. Using tilted magnetic fields, we have found that the enhanced effective mass is independent of the degree of spin polarization, which points to a spin-independent origin of the mass enhancement and is in contradiction w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
138
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(167 citation statements)
references
References 29 publications
26
138
3
Order By: Relevance
“…There is no need to invoke any non-Fermi liquid concepts to explain the recent experimental results on quasiparticle renormalization effects 3,4,5,6,7,8,9,10,11 . This work is supported by the NSF, the DARPA, the US-ONR, and the LPS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is no need to invoke any non-Fermi liquid concepts to explain the recent experimental results on quasiparticle renormalization effects 3,4,5,6,7,8,9,10,11 . This work is supported by the NSF, the DARPA, the US-ONR, and the LPS.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a number of experimental papers appearing in the recent literature reporting the lowtemperature ( 100mK) measurement of the susceptibility 3,4,5,6,7,8,9 and effective mass 10,11 in 2D electron systems as a function of carrier density in the r s ≈ 1 − 10 parameter range. Although some aspects of the data in different experiments (and more importantly, the interpretation of the data) have been controversial -most especially on the issue of whether there is a spontaneous density-driven ferromagnetic spin polarization transition at low carrier densities in 2D systems -the experimental reports convincingly establish a strong enhancement in both the spin susceptibility and effective mass as a function of decreasing (increasing) carrier density n (interaction parameter r s ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the highly interacting, dilute regime (r s > ∼ 3), χ * and m * are typically enhanced compared to the band values and increase with increasing r s , as confirmed both theoretically [1][2][3][4][5][6][7][8] and experimentally. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Besides r s , the spin and/or valley degrees of freedom also play an important role in the re-normalization of m * and χ * since they modify the exchange interaction. 5,6,17,[24][25][26][27] In particular, it was recently demonstrated that when a 2D electron system is fully spin and valley polarized, m * is suppressed compared to its band value.…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Besides r s , the spin and/or valley degrees of freedom also play an important role in the re-normalization of m * and χ * since they modify the exchange interaction. 5,6,17,[24][25][26][27] In particular, it was recently demonstrated that when a 2D electron system is fully spin and valley polarized, m * is suppressed compared to its band value. [24][25][26][27] This suppression was reproduced in subsequent, numerical theoretical work.…”
mentioning
confidence: 99%